2013
DOI: 10.1148/radiol.12120859
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Nonenhanced MR Angiographic Subtraction Techniques for Infragenual Arteries at 1.5 T: A Preliminary Study

Abstract: http://radiology.rsna.org/lookup/suppl/doi:10.1148/radiol.12120859/-/DC1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 36 publications
0
27
0
Order By: Relevance
“…Image quality of QISS-MRA was non-diagnostic in 2-3 % of the vessel segments. Non-diagnostic Vessel segments: Aorta (1), AIC right and left common iliac artery (2, 3), AIE right and left external iliac artery (4,5), AFC right and left common femoral artery (6, 7), AFP right and left deep femoral artery (8,9), AFS right and left proximal and distal superficial femoral artery (10)(11)(12)(13), AP right and left proximal, middle, and distal popliteal artery (14)(15)(16)(17)(18)(19), ATA right and left proximal and distal anterior tibial artery (20)(21)(22)(23), TFT right and left tibiofibular trunk (24,25), PTA right and left proximal and distal posterior tibial artery (26)(27)(28)(29), and AF right and left proximal and distal fibular artery (30)(31)(32)(33) image quality was attributed to off-resonance artifacts. Off-resonance refers to a deviation of the local spins' resonant frequency in relation to the nominated scanner center frequency and is caused by main field inhomogeneities or magnetic susceptibilities [21].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Image quality of QISS-MRA was non-diagnostic in 2-3 % of the vessel segments. Non-diagnostic Vessel segments: Aorta (1), AIC right and left common iliac artery (2, 3), AIE right and left external iliac artery (4,5), AFC right and left common femoral artery (6, 7), AFP right and left deep femoral artery (8,9), AFS right and left proximal and distal superficial femoral artery (10)(11)(12)(13), AP right and left proximal, middle, and distal popliteal artery (14)(15)(16)(17)(18)(19), ATA right and left proximal and distal anterior tibial artery (20)(21)(22)(23), TFT right and left tibiofibular trunk (24,25), PTA right and left proximal and distal posterior tibial artery (26)(27)(28)(29), and AF right and left proximal and distal fibular artery (30)(31)(32)(33) image quality was attributed to off-resonance artifacts. Off-resonance refers to a deviation of the local spins' resonant frequency in relation to the nominated scanner center frequency and is caused by main field inhomogeneities or magnetic susceptibilities [21].…”
Section: Discussionmentioning
confidence: 99%
“…Another promising nonenhanced MRA technique for assessment of PAD is subtraction MRA. Recent studies demonstrated that nonenhanced subtraction MRA allows assessment of PAD with high image quality [23,24]. However, several studies also revealed the drawbacks of nonenhanced subtraction MRA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach was established recently with superior sensitivity and specificity. 21 The MRI perfusion and oxygenation measurements were subsequently performed at rest and during a sustained isometric contraction of the plantar flexor muscles, which included the gastrocnemius and soleus muscles. Specifically, each measurement started at 2 minutes after the start of contraction, resulting in a total contraction time of approximately 3 minutes for a perfusion measurement and 6 minutes for an oxygenation measurement (see Imaging Methods section).…”
Section: Methodsmentioning
confidence: 99%
“…These include fresh-blood imaging, quiescent-interval single-shot (QISS) imaging, and flow-sensitizing dephasing gradient-prepared steady-state free precession imaging [20,25,[27][28][29][30]. QISS MRA has good accuracy and robustness for PAD assessment, specifically in diabetic patients, with an estimated sensitivity of 87.0-89.7% and specificity of 94.6-96.5% using gadolinium-enhanced MRA for comparison [23,26].…”
Section: Introductionmentioning
confidence: 99%